BROAD DISTRIBUTION OF CRYSTAL-FIELD ENVIRONMENTS FOR ND3+ IN CALCITE - Withers S.H.; Peale R.E.; Schulte A.F.; Braunstein G.; Beck K.M.; Hess W.P.; Reeder R.J. (My University, 2003)
Calcite micro-crystals were grown from solution with single crystal dimensions up to 3 mm and doped up to ~0.1% with Nd3+ ions. Phase purity was verified by powder x-ray diffraction. The concentration of Nd3+ was measured by energy-dispersive spectrometry and Rutherford backscattering spectrometry. Micro x-ray fluorescence mapping of the calcite grains indicates uniform Nd distribution in as-grown crystal grains. X-ray absorption fine structure indicates that Nd3+ is substituted for Ca2+ with local lattice distortion. Temperature dependent near-infrared spectroscopy of Nd3+ impurities in calcite reveals large inhomogeneous line widths. These results suggest a broad distribution of crystal-field environments for Nd3+ as a result of charge compensation and inhomogeneous lattice strain.
Keywords: Calcium carbonate; Calcite; Neodymium; Carbonate minerals; Nuclear waste